Studies on the Suitability of Origanum vulgare Seed Oil in Paint and Varnish Industry - Karnik, M. G.; Sharma, O. P.; Dobhal, N. P. (Indian Forester, 1966)
Drying properties of Origanum vulgare seed oil are described.